External Ring Annuloplasty: A Safe Landing Zone for Transcatheter Aortic Valve Replacement - Moiroux-Sahraoui, Alexander; Farge, Arnaud; Zacek, Pavel; Lansac, Emmanuel (The Annals of thoracic surgery, 2023)
Aortic stenosis in patients with previous valve-sparing root replacement represents a challenge, given the substantial morbidity and mortality rates in case of reoperation. Here, we present the case of a patient with late severe aortic stenosis 12 years after valve-sparing aortic root replacement. He was successfully treated by transapical aortic valve implantation. External ring annuloplasty, by reducing the native annuloaortic ectasia, allows transcatheter aortic valve replacement in case of stenotic deterioration of the native valve after valve-sparing aortic root replacement.
Keywords: transkatetrální implantace aortální chlopně; chirurgická náhrada chlopně; srdeční chlopně umělé; Aortic Valve; Aortic Valve Stenosis; lidé; mužské pohlaví; výsledek terapie; Male; aortální insuficience; Transcatheter Aortic Valve Replacement; Heart Valve Prosthesis Implantation; aortální chlopeň; Aortic Valve Insufficiency; Heart Valve Prosthesis; Treatment Outcome; aortální stenóza; Humans